2018
DOI: 10.13169/polipers.15.3.0099
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming Residential Prosumers in Energy Sector

Abstract: With the evolution of Solar PV technology, old paradigm of consumers being passive recipients is changing fast. Distributed generation with the help of end-users can be instrumental in realizing goals of making the energy sector more decentralized, decarbonized and democratized. Against the backdrop, residential prosumers have occupied central role in the transition debate. If adequately empowered, they can prove the change agents for facilitating integration of renewables and building a more sustainable futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Growing attention is being paid to business models in a post-subsidy market that can offer new value propositions to energy prosumers (Karami & Madlener, 2022). The term 'prosumer' refers to a person or entity who consumes and produces energy, resulting in a two-way ow of energy (Saleh, 2018;Parag & Sovacool, 2016). Private energy prosumers, a relevant group of active agents in the energy system, strategically exchange energy with the utility grid or other prosumers (Dütschke, et al, 2021).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Growing attention is being paid to business models in a post-subsidy market that can offer new value propositions to energy prosumers (Karami & Madlener, 2022). The term 'prosumer' refers to a person or entity who consumes and produces energy, resulting in a two-way ow of energy (Saleh, 2018;Parag & Sovacool, 2016). Private energy prosumers, a relevant group of active agents in the energy system, strategically exchange energy with the utility grid or other prosumers (Dütschke, et al, 2021).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The prosumer roles include the Market Participation Strategy (MPS), Strategic Analysis; Competitive Advantage; Economic evaluation and benefits; Business research. Also, the Prosumer is a potential solution to achieving trade in renewable energy [61]. In [62], the authors have shown that energy providers have several objectives with the integration of Prosumer features: providing electricity demand for consumers, integrating IT, and reducing prices.…”
Section: Sg Emerging Issuesmentioning
confidence: 99%
“…Some energy rules aim to make renewable energy more cost-effective; however, it is difficult to estimate the costs of adopting renewable energy sources. Energy consumption is evaluated using the LCOE and ESA cost-evaluation methods [ 60 ]. The SG system contains many components for power distribution.…”
Section: Preliminaries: Detailed Analysis Of the Literaturementioning
confidence: 99%